Antioxidant and Cytotoxic Activities of Aerial and Underground Parts of Hypericum Scabrum L. - Karatoprak, Gokce Seker; Yucel, Cigdem; Kaytan, Hasan Cagri; Ilgun, Selen; Safak, Esra Kongul; Kosar, Muberra (Springer International Publishing Ag, 2019)
We have studied Hypericum scabrum L. plant which belongs to the Hypericaceae family, naturally growing in Anatolia. The aim of this research is to investigate the chemical composition (total phenol, total flavonoid) of 70% methanol and water extracts prepared from the underground and flowering aerial parts to investigate the antioxidant and cytotoxic activity. In order to determine the antioxidant activities of the extracts, 1,1-diphenyl-2-picrylhydrazyl (DPPH), 2,2 '-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) radical scavenging activities and the inhibition of beta-carotene/linoleic acid co-oxidation were studied. In cytotoxicity experiments, 3-(4,5-dimethylthiazol-2-yl) -2,5-diphenyltetrazolium (MTT) method was used on human lung cancer cell line (A549), human colon adenocarcinoma cell line (COLO 205) and mouse fibroblast (L929) cell line. When the chemical composition of the extracts was examined, the richest extract in terms of total phenolic content was found to be water extract prepared form the flowering part of the plant, and this extract was evaluated to be more active in DPPH radical scavenging activity test than the other extracts. In the cytotoxicity assays, 70% methanol extracts prepared from the flowering and root parts of the plant showed more inhibitory effects on cell viability than water extracts. Our experimental evidence suggests that these Hypericum extracts may be useful as antioxidant and cytotoxic agents.
Keywords: Hypericum scabrum; Hypericaceae; Antioxidant; Cytotoxic